When Visuals Speak: The Impact of Accentations on Decision Outcomes - Novita Putri Ardiana; Mohamad Rifqy Roosdhani; Anna Widiastuti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study investigates how visual accentuation influences re-election intention among Generation Z, with visual appeal and self-brand congruence as mediating factors. The study focuses on the 2024 Indonesian Legislative Election, examining a campaign that used a distinctive visual strategy featuring a popular fictional character. A quantitative approach was applied, with data collected from 400 Generation Z respondents in the Central Java II electoral district. Structural Equation Modeling Partial Least Squares (SEM PLS) was used to analyze the relationships among visual accentuation, visual appeal, self-brand congruence, and re-election intention. The results indicate that visual accentuation significantly affects re-election intention. Stronger effects occur indirectly through visual appeal and self-brand congruence than through direct exposure alone, suggesting that psychological evaluations enhance the impact of visual elements on voter behavior. These findings highlight the importance of designing political campaigns that leverage visual strategies to engage younger voters effectively. The study provides practical guidance for political communication and lays the foundation for future research on visual-based persuasion in electoral contexts.